Predictive validity and correlates of self‐assessed resilience among U.S. Army soldiers. Issue 2 (2nd November 2017) - Campbell‐Sills, Laura; Kessler, Ronald C.; Ursano, Robert J.; Sun, Xiaoying; Taylor, Charles T.; Heeringa, Steven G.; Nock, Matthew K.; Sampson, Nancy A.; Jain, Sonia; Stein, Murray B.
Abstract : Background: Self‐assessment of resilience could prove valuable to military and other organizations whose personnel confront foreseen stressors. We evaluated the validity of self‐assessed resilience among U.S. Army soldiers, including whether predeployment perceived resilience predicted postdeployment emotional disorder. Methods: Resilience was assessed via self‐administered questionnaire among new soldiers reporting for basic training ( N  = 35, 807) and experienced soldiers preparing to deploy to Afghanistan ( N  = 8, 558). Concurrent validity of self‐assessed resilience was evaluated among recruits by estimating its association with past‐month emotional disorder. Predictive validity was examined among 3, 526 experienced soldiers with no lifetime emotional disorder predeployment. Predictive models estimated associations of predeployment resilience with incidence of emotional disorder through 9 months postdeployment and with marked improvement in coping at 3 months postdeployment. Weights‐adjusted regression models incorporated stringent controls for risk factors. Results: Soldiers characterized themselves as very resilient on average [ M  = 14.34, SD = 4.20 (recruits); M  = 14.75, SD = 4.31 (experienced soldiers); theoretical range = 0–20]. Demographic characteristics exhibited only modest associations with resilience, while severity of childhood maltreatment was negatively associated with resilience in both samples. Among recruits, resilience was inversely associated with past‐month emotional disorder [adjusted odds ratio (AOR) = 0.65, 95% CI = 0.62–0.68, P  < .0005 (per standard score increase)]. Among deployed soldiers, greater predeployment resilience was associated with decreased incidence of emotional disorder (AOR = 0.91; 95% CI = 0.84–0.98; P  = .016) and increased odds of improved coping (AOR = 1.36; 95% CI = 1.24–1.49; P  < .0005) postdeployment. Conclusions: Findings supported validity of self‐assessed resilience among soldiers, although its predictive effect on incidence of emotional disorder was modest. In conjunction with assessment of known risk factors, measurement of resilience could help predict adaptation to foreseen stressors like deployment.